Computer-assisted clinical coding: A narrative review of the literature on its benefits, limitations, implementation and impact on clinical coding professionals. Issue 1 (January 2020) - Campbell, Sharon; Giadresco, Katrina
Background: Information technology has the potential to streamline processes in healthcare for improved efficiency, quality and safety, while reducing costs. Computer-assisted clinical coding (CAC) has made it possible to automate the clinical coding process by assigning diagnoses and procedures from electronic sources of clinical documentation. Implementation of CAC requires both investigation of the clinical coding workflow and exploration of how the clinical coding professional's role might change and evolve as a result of this technology. Objective: To examine the benefits and limitations of CAC technology; best practices for CAC adoption; the impact of CAC on traditional coding practices and roles in the inpatient setting. Method: This narrative review explores the current literature available on CAC. Literature indexed in ProQuest, Medline and other relevant sources between January 2006 and June 2017 was considered. Results: A total of 38 journal articles, published dissertations and case studies revealed that CAC has demonstrated value in improving clinical coding accuracy and quality, which can be missed during the manual clinical coding process. Conclusion: Clinical coding professionals should view CAC as an opportunity not a threat. CAC will allow clinical coding professionals to further develop their clinical coding skills and knowledge for future career progression into new roles such as clinical coding editors and clinical coding analysts. Sound change management strategies are essential for successful restructuring of the clinical coding workflows during the implementation of CAC.